Analisa Jejaring Sosial Terhadap Fenomena Cyberbullying Fandom K-Pop pada Sosial Media Twitter - Ghufron, Mohammad Iqbal; Supriyati, Endang; Listyorini, Tri (UIN Sunan Kalijaga Yogyakarta, 2024)
This study examines cyberbullying among K-pop fandoms through social network analysis (SNA) using data from Twitter, a social media platform. The phenomenon of K-pop gaining global popularity also brings negative impacts, such as cyberbullying, which can affect the psychological well-being of victims. Using R Studio and Gephi analysis tools, this study applied centrality values, including degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality, to identify influential accounts in the spread of the cyberbullying phenomenon. This analysis provides insight into the interaction and influence between Twitter user accounts in the context of cyberbullying. The main objective of this research is to paint a picture of the cyberbullying phenomenon involving various K-pop fandoms and identify the accounts that play an essential role in the related communication network.